Social values depicted in the Aklat Adarna's International Edition series a content analysis - Soriano, Ma. Bettina T. (Institute of Library Science, University of the Philippines Diliman, 1997)
This is intended to examine the worth of Aklat Adarna's International Edition series as a potential tool for teaching social values to children. To determine the social values depicted in Aklat Adarna's International Edition, a content analysis was conducted by first giving brief descriptions of each story based on the literary components of theme, plot, character, and setting and then by giving each story a qualitative evaluation based on the identification and tabulation of the social values it depicts.